Religion and world peace - Kumar, Ravindra (New Delhi : Eastern Book Linkers, 2014)
Contributed research papers chiefly with reference to India.
Includes bibliographical references and index.
Keywords: Nonviolence -- Religious aspects; Peace -- Religious aspects; Nonviolence -- Religious aspects; Peace -- Religious aspects; India -- Religion